Produção integrada de etanol 1G/2G utilizando meios industriais e leveduras recombinantes - Pereira, Laís Portugal Rios da Costa (2021)
Second generation (2G) ethanol is an alternative to increase the supply of this biofuel without expanding the sugarcane plantation area and to utilize the excess of sugarcane bagasse available in Brazil due to the intense economic activity related to sugar and alcohol production. Due to the advances in Molecular Biology, Saccharomyces cerevisiae strains capable of assimilating and fermenting xylose, the main sugar present in the hemicellulosic fraction of lignocellulosic materials, have been developed. However, the low tolerance of these yeasts to hemicellulose hydrolysates inhibitors (acetic acid, hydroxymethylfurfural, furfural and phenolic compounds) and to ethanol leads to loss of cell viability and to low fermentation rates and ethanol productivities, compromising the performance and economic viability of the fermentation process. Thus, the development of more efficient production processes to obtain high ethanol concentrations, compatible with those required in the distillation step, from hemicellulose hydrolysates with high sugar concentrations, is necessary. Process improvement depends both on the availability of yeast strains that are more tolerant to inhibitors and on operating strategies that minimize the effects of the inhibitors. On the other hand, the incorporation of by-products from the sugar and alcohol industry, such as molasses, in the composition of the medium for the production of 2G ethanol favors the flexibility and economic viability of the process. In this context, the present study aimed to evaluate strategies to establish a robust and scalable process for obtaining 2G ethanol under industrial fermentation conditions and to promote the integration of 1G and 2G ethanol production. The performance of three latest generation recombinant yeasts (S. cerevisiae GSE16-T18, GSE16-T18 HAA1 and MDS 130), immobilized on calcium alginate gel, was evaluated in in natura sugarcane bagasse hemicellulose hydrolysate, obtained from acid pre-treatment (not concentrated), supplemented or not with molasses. Synthetic media were also evaluated as a control. The experiments were carried out in repeated batches in minireactors and in a fixed bed reactor and fermentations were accompanied by carbon dioxide production and by analysis of reducing sugar concentration, respectively. The concentration of sugars and metabolites in the supernatant was determined by High Performance Liquid Chromatography (HPLC) and the viability of the cells by the methylene blue technique. It was found that, unlike concentrated hemicellulose hydrolysates, the concentration of inhibitors present in in natura hemicellulose hydrolysate does not severely impact the fermentation performance. The supplementation with molasses proved to be an efficient strategy to achieve high fermentable sugar concentration, allowing to obtain productivities of up to 23 g/L/h and prolonged operation in repeated batches, compatible with the industrial operation. The toxic effect of high ethanol concentrations (above 80 g/L) on cell viability was observed for all strains and limited cell recycling to a maximum of five repeated batches. The performance of the strains in terms of conversion of fermentable sugars and productivity and yield in ethanol was similar, with the exception of MDS 130, which was unable to efficiently assimilate xylose in the presence of high hexose (glucose and/or fructose) concentration.